О композиции и нетеровости операторов в векторных пространствах - Плакса, С.А. (Український математичний журнал, 1993)
Under the minimal assumptions imposed on given spaces, the sufficient conditions are established, under which the composition BA of operators A and B has the Noether property and is normally solvable. Similar conditions, guaranteeing that the operatorA is normally solvable or possesses the Noether property, are obtained for the operators B and BA.